Patient positioning in radiotherapy based on surface imaging using time of flight cameras. Issue 8 (28th July 2016) - Gilles, M.; Fayad, H.; Miglierini, P.; Clement, J. F.; Scheib, S.; Cozzi, L.; Bert, J.; Boussion, N.; Schick, U.; Pradier, O.; Visvikis, D.
Abstract : Purpose: To evaluate the patient positioning accuracy in radiotherapy using a stereo‐time of flight (ToF)‐camera system. Methods: A system using two ToF cameras was used to scan the surface of the patients in order to position them daily on the treatment couch. The obtained point clouds were registered to (a) detect translations applied to the table (intrafraction motion) and (b) predict the displacement to be applied in order to place the patient in its reference position (interfraction motion). The measures provided by this system were compared to the effectively applied translations. The authors analyzed 150 fractions including lung, pelvis/prostate, and head and neck cancer patients. Results: The authors obtained small absolute errors for displacement detection: 0.8 ± 0.7, 0.8 ± 0.7, and 0.7 ± 0.6 mm along the vertical, longitudinal, and lateral axes, respectively, and 0.8 ± 0.7 mm for the total norm displacement. Lung cancer patients presented the largest errors with a respective mean of 1.1 ± 0.9, 0.9 ± 0.9, and 0.8 ± 0.7 mm. Conclusions: The proposed stereo‐ToF system allows for sufficient accuracy and faster patient repositioning in radiotherapy. Its capability to track the complete patient surface in real time could allow, in the future, not only for an accurate positioning but also a real time tracking of any patient intrafraction motion (translation, involuntary, and breathing).